DEVELOPMENT OF AI-BASED E-MODULES IN THE SUBJECT OF MORAL BELIEFS MADRASAH ALIYAH - Ilham Putra Pratama; Mardianto; Salminawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to develop and evaluate the effectiveness of an Artificial Intelligence (AI)-based e-module for the Akidah Akhlak subject at Madrasah Aliyah, focusing on the topic of commendable morals, namely Hikmah, Iffah, Syajaah, and A’dalah. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The study was conducted at MAN 2 Deli Serdang involving Grade X students. Data were collected through observations, interviews, questionnaires, expert validations, and pre-test and post-test assessments. The e-module was developed using Google Sites, Canva AI, and Google Gemini to provide interactive, adaptive, and student-centered learning experiences. Validation results indicated that the material expert assessment reached 88.6%, while the media expert assessment reached 77.5%, both categorized as highly feasible. Field testing showed positive student responses, with individual trials achieving 85.84% and group trials reaching 92.5%, indicating a very feasible product. Effectiveness testing demonstrated a significant improvement in learning outcomes, where the experimental class average increased from 52.91 in the pre-test to 83.54 in the post-test, outperforming the control class. Statistical analysis using a paired sample t-test showed a significant difference (p < 0.001). These findings indicate that the AI-based e-module is highly feasible and effective in improving student engagement, motivation, and learning outcomes in Akidah Akhlak learning.